2014
DOI: 10.1016/j.cub.2013.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia Actin-Based Motility Occurs in Distinct Phases Mediated by Different Actin Nucleators

Abstract: Summary Many intracellular bacterial pathogens undergo actin-based motility to promote cell-cell spread during infection [1]. For each pathogen, motility was assumed to be driven by a single actin polymerization pathway. Curiously, spotted-fever-group Rickettsia differ from other pathogens in possessing two actin polymerizing proteins. RickA, an activator of the host Arp2/3 complex, was initially proposed to drive motility [2, 3]. Sca2, a mimic of host formins [4, 5], was later shown to be required for motilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
170
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(182 citation statements)
references
References 35 publications
10
170
0
1
Order By: Relevance
“…Similar to Listeria monocytogenes , SFGR use an actin comet tail mechanism for motility. Yet, unlike Listeria and other pathogens that use actin-driven motility, SFGR use two independent actin polymerization pathways [38]. Thus, early after infection motility is slow, driven by short and curved comet tails that are formed by RickA, an NPF expressed on the surface of the bacterium that recruits and activates the host cell Arp2/3 complex.…”
Section: Opinionmentioning
confidence: 99%
“…Similar to Listeria monocytogenes , SFGR use an actin comet tail mechanism for motility. Yet, unlike Listeria and other pathogens that use actin-driven motility, SFGR use two independent actin polymerization pathways [38]. Thus, early after infection motility is slow, driven by short and curved comet tails that are formed by RickA, an NPF expressed on the surface of the bacterium that recruits and activates the host cell Arp2/3 complex.…”
Section: Opinionmentioning
confidence: 99%
“…However, very recent research on R . parkeri demonstrated that RickA and Sca2 each direct independent modes of ABM, with RickA generating short, curved actin tails early during infection and Sca2 generating long, straight actin tails later in infection (Reed et al ., 2014) . This is partially consistent with a previous suggestion that RickA targets actin for the facilitation of host cell entry (Haglund et al ., 2010) , but reveals that RickA-induced HAP, like that of Sca2, can facilitate intercellular spread in some species.…”
Section: Secretory Proteins At the Host Interfacementioning
confidence: 99%
“…These proteins act processively on barbed ends in which they sit during the entire polymerization process. Interestingly, while Listeria and Shigella use Arp2/3, the intracellular pathogens Rickettsia early in infection use Arp2/3 and later on switch to a different mechanism, expressing proteins that mimic formins to promote actin-based motility (Welch et al, 1998;Suzuki et al, 1998;Gouin et al, 2004;Reed et al, 2014) (see below and Figure 1). …”
mentioning
confidence: 99%
“…In the case of Shigella, the outer-membrane protein IcsA/VirG (Bernardini et al, 1989) recruits N-WASP (Suzuki et al, 1998), which in turn recruits and activates Arp2/3 (Figure 1). In Rickettsia, early during infection, the protein RickA, which displays a VCA domain, mimics WASP family proteins and recruits Arp2/3 (Gouin et al, 2004;Reed et al, 2014). Later, the surface protein Sca2 acts as a formin (Reed et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation